Topical gel containing Polysiloxanes and hyaluronic acid for skin scar: Formulation design, characterization, and In vivo activity. (6th January 2023) - Alam, Md. Shoaib; Ansari, Arif; Ahsan, Iftikhar; Shafiq‐un‐Nabi, Sheikh; Md, Shadab; Shaik, Rasheed A.; Eid, Basma G.; Ahmad, Mohammad Zaki; Ahmad, Javed
Abstract: Background: Scar formation is undesirable both cosmetically and functionally. It shows that silicone gel is effective in preventing and improving scars formed due to a wound formation after injury. Objectives: This study investigates whether a silicone gel composition based on a novel concept of infusing a biologically active material such as hyaluronic acid and/or salts with various polysiloxane derivatives in a specific proportion to achieve desired viscosity range and their action has a synergistic beneficial effect on skin scar after injury. Methods: We have developed a topical gel utilizing a combination of emulsifiers, sodium hyaluronate, polysiloxane, and its derivatives. The method of preparation comprises mixing of aqueous phase dispersion and polysiloxanes blend under stirring at room temperature. Results: It results in the formation of a homogenous smooth gel formulation. The developed topical gel formulation was characterized for physicochemical properties, rheology, stability, and anti‐scar activity in Wistar rats. It was found that the developed formulation system consists of desirable attributes for skin applications. In vivo investigation of developed polysiloxane gel formulation for anti‐scar activity shown promising outcomes compared to marketed product (Kelo‐cote scar gel). Furthermore, a histopathology study of healed skin tissues observed the formation of microscopic skin structures compared to the Kelo‐cote scar gel. Conclusions: It indicates that the combination of polysiloxanes and sodium hyaluronate resulting an improvement in anti‐scar activity compared to the marketed product containing polysiloxanes alone.